Phasing Out Payroll Tax Subsidies - Anna Herget; Regina T. Riphahn (Institute of Labor Economics (IZA), 2024)
Many countries subsidize low-income employments or small jobs. These subsidies and their phasing out can generate labor market frictions and distort incentives. The German Minijob program subsidizes low-income jobs. It generates a 'Minijob trap' with substantial bunching along the earnings distribution. Since 2003, the newly introduced Midijob subsidy aims to reduce the Minijob-induced notch in the net earnings distribution. Midijobs reduce payroll taxes for employments above the Minijob earnings ceiling. We investigate whether introducing Midijobs reduced the Minijob trap. We apply a regression discontinuity design using administrative data and a difference-in-differences estimation using survey data. While in both cases our results show a small positive overall effect of Midijobs on transitions out of Minijobs, they are effective only for a narrow treatment group.
Keywords: J21; J38; H24; 330; Midijobs; Minijobs; payroll tax subsidy; causal effects; difference-in-differences; regression discontinuity; SOEP; SIAB